Effect of precipitate hardening treatment on microstructure and mechanical properties of cast aluminum silicon alloy (A356) - Bindamin, Benjunior (2012)
The main objective of this work was to study the influence of the precipitate hardening treatment of the A356 aluminum silicon sand cast alloy. The experiment process was separated into three parts which was foundry laboratory, material laboratory, and inspection. In the foundry laboratory, the cast alloys was prepared by sand casting process and was melted in a diesel furnace. In the material laboratory, the casting was then treated with precipitate hardening treatment and followed by machining. The inspection was done to observe microstructure, tensile properties and hardness properties. The effect of the solution heat treatment and artificial aging holding time on the microstructure, tensile properties, and hardness properties of the alloy was analyzed. Three specimens were heat treated with a solution treatment at a same temperature of 540°C, was quenched in room temperature water followed by artificial aging at a same temperature of 170°C. The different parameters were holding times which were solution at 2 hours and aging 2 hours, solution at 2 hours and aging 6 hours, solution 6 hours and aging 6 hours. The microstructure were investigated and tested by optical microscope, tension test and Rockwell hardness test respectively. The result found was at 2 hours solution of 540 °C homogenization and saturation of magnesium and silicon in Į(Al) phase, spheroid of eutectic Si phase occurred. After solution treatment, 2 hours artificial aging at 170 °C produced hardening precipitates. Samples treated at 6 hours solution and 6 hours artificial aging achieved even higher tensile strength and hardness. The increased of holding time for solution and artificial aging increased precipitate hardening.